IMPLEMENTING THE VALUES OF TOLERANCE IN RELIGION-BASED SCHOOLS (Case study at Marsudirini Elementary School Yogyakarta) - Ari Wibowo; Yossi Dyah Apriliani (Elementary School: Jurnal Pendidikan dan Pembelajaran ke-SD-an, 2022)
This study aims to determine the implementation of the cultivation of religious tolerance values in Marsudirini Elementary School Yogyakarta. This type of research is a qualitative case study. Determination of research subjects with purposive sampling technique. The subjects of this study were the principal, class teacher of fourth grade students. Collecting data in this study using interviews, observation and documentation. The data analysis technique used is descriptive qualitative. The data validity technique uses source triangulation and technical triangulation. The results of the study conclude that 1) planning for the cultivation of religious tolerance values through school policies, namely through the vision, mission, goals, and rules. 2) Instilling the value of religious tolerance through four strategies, namely: a) habituation of exemplary; b) routine habituation; c) spontaneous habituation; d) conditioning. 3) supporting and inhibiting factors for inculcating religious tolerance values, namely a) student factors; b) family factors (parents); c) school factors; d) infrastructure factors.